Management of Type II Diabetes by Modulating the Modifiable Risk Factors: A Future Roadmap for Prevention of Cerebrovascular Complications. Issue 3 (July 2020) - Sharma, Kanupriya; Battu, Priya; Anand, Akshay; Nagarathna, Raghuram; Kaur, Navneet; Malik, Neeru; Singh, Amit; Nagendra, Hongasandhra R
Background: Indian Diabetes Risk Score (IDRS) is a screening tool for quantifying the risk of diabetes mellitus (DM) development in the Indian population. The present study has evaluated the level of risk of developing DM in Chandigarh and Panchkula based on the IDRS score. Methods: As a part of a national diabetes control trial funded by the Ministry of Health and Family Welfare (MoHFW) and the Ministry of AYUSH, Government of India, 1, 916 participants from the Chandigarh and Panchkula regions were assessed for the risk of developing DM. Risk assessment was done on the basis of the IDRS score which includes age, family history, waist circumference, and physical activity as its contributing factors. Participants with an IDRS score <30 were in the low-risk category, those with 30 to 50 were in the moderate-risk category, and those with >60 were in the high-risk category for DM. Results: Out of the 1, 916 screened respondents (59.86% females and 40.14% males), 894 participants (46.65%) were at a high risk for DM (IDRS >60), 764 (39.87%) were at a moderate risk (IDRS = 30–60), and 258 (13.46%) were at a low risk (IDRS <30). Waist circumference contributed to 35.90% of the high-risk category followed by age (19.67%) and physical activity (11.67%). Age and waist circumference also showed a strong correlation with the total IDRS score. Conclusion: The Chandigarh and Panchkula population showed a high tendency to develop DM based on the IDRS score. Modifiable risk factors such as waist circumference and physical activity were the major contributing factors. Apart from the modifiable risk factors, age was also another major contributing risk factor. Based on these outcomes, lifestyle modifications like yoga and exercise can be proposed for this population as a preventive approach to reduce the risk of developing DM and other associated cerebrovascular complications.